(3cTa GdbfGY Yf hLg GdOdjd aj QO ef bGd aj GdQVGY HGdJfRjds - (3GdOQGRj, GdHMQGfj, GHf YUahQ, jhSa Hf CMeO Hf EHQGgje, J(B1186(3g`s ((3Ydj Hf eMeO Hf ESMGb GdehShj GdHZOGOjs)
(3ChdgG (B:s
(3fMeOc jG ef habfG dGQJVGY dHGf GdYdhe(B... (3hHYO ajbhd(B... (3jhSa Hf CMeO(B... (3gPg cdeGJ TQjaI JJYdb HCMcGe GdQVGY(B...s
(3BNQgG (B:s
(3hcPG faS GdEbQGQ EdG Cf jYde GSJfGOg Edi ePgH jNGda ePgH GdSGeY(B... (3hgPG BNQ eG bUOfG EjQGOg aj gPg GdQSGdI(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B8(3, U(B215s
(3gOjI GdYGQajf(B: (3L(B2(3, U(B569s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis